Jorge Peixinho's interpretative gestures reflected in his guitar music: analysis and performance - Baptista, Pedro (2019)
The present communication proposal is inserted in the scope of the Investigation Project “Jorge Peixinho and the guitar”. The project consists on the framework of Jorge Peixinho's works with guitar, identification of the specificities of the composer's writing for the guitar and exploration of technical and musical implications on performance. This communication is born from the investigation problem visible in the following question: how to interpret Jorge Peixinho's guitar works? The aim is to create interpretation proposals grounded on the options taken by the composer as a performer. Recordings of the pianist Jorge Peixinho performing his own piano works were collected and analyzed. This way, it has been identified reoccurring interpretative gestures characteristic to Peixinho. These gestures are synthesized on a dictionary that presents a range of possibilities, intended to create a restitution of interpretative gestures of the pianist/composer. Based on this tool, there is an exploration of the identified gestures' application to analogous sections found on Jorge Peixinho's guitar manuscripts (1971 to 1994). Through the recording's analysis and identification of gestures, a dictionary is created whose consultation could interest all the performers that want to have an approach to Jorge Peixinho's lifeworks, as a tool of reference, contextualization and/or fertilization of the performance. Through the exploration of the identified gestures' concrete application to the repertoire with guitar in particular, interpretation proposals pertinent to guitarists that are interested in Jorge Peixinho's work were born. The communication will include a reproduction of recordings (video) of interpretative proposals on the guitar, as well as excerpts of the recordings (audio) of Jorge Peixinho.